Variabilidade temporal do índice de vegetação por diferença normalizada obtido por sensor ativo de reflectância nas culturas de milho, soja e trigo - Beneduzzi, Humberto Martins (2015)
Currently, optimizing the management of nitrogen fertilizers has been one of the great challenges in grain production, since N has the potential to increase yield, but if it is applied in excess, it can cause environmental damage due to the leaching process. Precision agriculture aims at solving this problem by applying fertilizer at different rates, in order to apply the right amount of fertilizer at each point of a certain cropped area. The N estimate is essential at each point and can be carried out by reflectance sensors, which is an equipment with proven efficacy in this task. Passive sensors, however, are directly influenced by solar radiation since they do not have an emission source, thereafter they use solar radiation to perform measurements. On the other hand, the active sensors could, in theory, be used at any time of the day and in different weather conditions, since they have their own emission source. In practice, some researches have already shown that even these devices are influenced by the amount of solar radiation and weather changes. Thus, this paper studied the temporal variability of the NDVI vegetation index, registered by an active reflectance sensor on crops such as maize, soybeans and wheat. The NDVI and irradiation data were collected by a GreenSeeker sensor at every 15 minutes over 12, 14 or 26 hours straight. The NDVI index was negatively influenced by irradiation in all experiments with maize, soybean and wheat. Thus, it has shown higher values at the beginning and end of the day and there also were changes in cloud cover that affected the NDVI in most experiments.